(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Despite the immense potential of wave energy, the economic viability of wave energy converters (WECs) remains a challenge. A key factor lies in the design and reliability of critical components such as mooring systems and . Accurate but efficient fatigue life assessment is essential for optimizing mooring line and dynamic cables designs to ensure long-term reliability under operational and extreme conditions. However, traditional time-domain fatigue analysis methods are computationally expensive, limiting their application during time-consuming iterative design processes. This study presents a novel frequency-domain (FD) approach for evaluating the dynamic response coupled to fatigue life in mooring systems for wave energy technologies. The method provides a computationally efficient alternative to time-domain simulations, enabling large-scale design space exploration and coupled optimization of the WEC and its moorings. The approach incorporates coupled platform-mooring dynamics directly by FD analysis and employs a spectral fatigue model combined with a mean stress correction method to efficiently account for the presence of mean stress in moorings, enhancing the accuracy of life predictions. The proposed methodology follows these steps: • Mooring line tensions and platform dynamics are calculated using FD simulations under various resource and operational conditions. • Spectral characteristics of the cyclic loads are derived from the dynamic analysis, integrating relevant stress factors. • Fatigue damage is assessed using spectral methods, and the lifetime is estimated based on environmental load spectra. • The methodology is applied to optimize mooring line design by adjusting parameters such as line length and diameter, ensuring fatigue life and performance criteria are met while minimizing material costs. By reducing computational requirements without compromising fidelity, this FD-based coupled approach offers a practical tool for preliminary design and optimization of WEC mooring systems. The methodology is demonstrated using the RM3 WEC as a case study and validated against time-domain simulations.